Localizing SDGs: the case of city planning in Malmö - Zinkernagel, Roland; Neij, Lena (Frontiers in Sustainable Cities, 2023)
Cities have an important role to play in implementing the UN Sustainable Development Goals (SDGs) and to mobilize sustainability at the urban level. Yet, municipalities encounter challenges in localizing the SDGs into their governance structures, and there is a need to advance our understanding of cities strengths and weaknesses in such processes. In this article we provide knowledge and reflections gained in analyzing the process of localizing the SDGs into the spatial planning of Smörkajen, a former industrial harbor site in Malmö, Sweden. By applying the analytical framework of Institutional Capacity Building, the study explores the process of localizing the SDGs in terms of building relational and knowledge capacities and to provide mobilization capacity by the formation of a sustainability strategy. The results illustrate an inclusive approach supporting relational capacity and numerous measures to enhance knowledge capacity, bringing about the formation of a draft sustainability strategy, strongly supported by the municipal participants. But rather than formally adopting the full strategy in the spatial planning of the Smörkajen area, the results of the process were only to be considered to the extent the traditional documents and processes allowed. In all, the results illustrate a strong support for the use of localized SDGs among municipal administrative units to mobilize sustainability, but also the challenges in actually implementing these in the formal planning and development process.